Aortic dissection causing 2 myocardial infarctions - Szabo, Sebastian; Hoffmeister, Hans Martin (Journal of Cardiology and Cardiovascular Medicine, 2019)
A 56-year-old man was admitted to our hospital because of sudden onset of right-sided thoracic pain. The ECG showed inferior ST segment elevations. He has been treated with aspirin, clopidogrel, unfractionated heparin and tenecteplase, and his symptoms resolved after 30 minutes. About half an hour later, the patient developed again left-sided thoracic pain and the signs of an anterior myocardial ST-segment elevation infarction. 90 minutes after receiving the initial medications, the performed coronary angiography revealed a long dissection of a large ramus circumflexus. Furthermore, the left anterior descending coronary artery was occluded at about the mid-level. The left ventriculography showed a reduced ventricular function and a Stanford type A aortic dissection. Immediate patient transfer for emergency surgical intervention was arranged. However, ventricular fibrillation occurred during transport and he required endotracheal intubation and prolonged cardiopulmonary resuscitation. Unfortunately, he died during further transport. In a patient with massive thoracic pain of initially uncommon localization in combination with fluctuation of ST-segment elevations, aortic dissection should be seriously taken into the differential diagnosis as well as into therapeutic management decisions (in particular antiplatelet and thrombolytic therapy).